When the Body Keeps the Score: Some Implications of Trauma Theory and Practice for Psychoanalytic Work. Issue 6 (17th August 2020) - Dent, Vivian
ABSTRACT: Trauma has wide-ranging effects on somatic functioning, nervous system regulation, relational engagement, and personality integration. This article provides an overview of how posttraumatic dysregulation and dissociation limit patients' ability to engage in an analytic process, potentially leading to prolonged, stalled, or ruptured treatments. In this context, it offers suggestions for integrating insights and techniques from trauma therapies into psychoanalytic work, focusing on interventions that help people modulate posttraumatic reactions and so build their capacities to work through trauma's impact.